2012
DOI: 10.1007/s00256-012-1430-5
|View full text |Cite
|
Sign up to set email alerts
|

The posterior transtriceps approach for intra-articular elbow diagnostics, definitely not forgotten

Abstract: The posterior transtriceps approach is a technical feasible procedure, is easy to perform, and avoids a diagnostic dilemma in presumed injuries to the lateral collateral ligament complex. Our results show a tendency of even lesser amount of contrast leakage, further promoting a more widespread usage of the posterior transtriceps approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Subsequently, 20 mL of saline was injected in the joint from posterior into the olecranon fossa. 38 Arthroscopy was performed by use of 6 portals: 1 proximal anteromedial, 1 proximal anterolateral, 2 posterior, and 2 posterolateral (Figure 2). A standard 30° wide-angle scope (5-mm diameter) was used to visualize the radiocapitellar compartment and address the osteochondral lesion.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, 20 mL of saline was injected in the joint from posterior into the olecranon fossa. 38 Arthroscopy was performed by use of 6 portals: 1 proximal anteromedial, 1 proximal anterolateral, 2 posterior, and 2 posterolateral (Figure 2). A standard 30° wide-angle scope (5-mm diameter) was used to visualize the radiocapitellar compartment and address the osteochondral lesion.…”
Section: Methodsmentioning
confidence: 99%
“…There was no contrast leakage in either of our two patients. If there was leakage, as in the cases previously reported by other authors [ 1 , 2 ], it would not affect the diagnostic quality of the MRI examination, unlike with a radiocapitellar approach. Additionally, another advantage of the transtriceps approach is that it can be transposed to ultrasound-guided arthrography [ 1 ].…”
Section: Discussionmentioning
confidence: 68%
“…In 2009, Lohman et al discussed the transtriceps approach for elbow arthrography and found that the major advantage was that if contrast leakage were to occur, it wouldn’t interfere with the diagnostic quality given the leakage wouldn’t interfere with the lateral structures, as would the case with a more conventional and commonly used radiocapitellar approach [ 1 ]. In 2012, Wagenberg et al reported studying a larger patient cohort using the transtriceps approach and found there is less contrast leakage compared to the radiocapitellar approach [ 2 ]. Furthermore, the transtriceps approach avoids damage to the radial collateral ligament [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, 20 mL of saline was injected into the joint from posterior into the olecranon fossa. 30 Arthroscopy was performed with 6 portals: 1 proximal anteromedial, 1 proximal anterolateral, 2 posterior, and 2 posterolateral. A standard 30° wide-angle scope (4 mm diameter) was used to visualize the radiocapitellar compartment and identify the osteochondral defect.…”
Section: Methodsmentioning
confidence: 99%